(untitled) (Modern education and development, 2025)
This article comprehensively analyzes the technology for processing plums (Prunus domestica L.) into jam, detailing the key stages: raw material selection, washing, pit removal, cooking, homogenization, pasteurization, and packaging. The study evaluates the technology’s impact on nutritional properties (vitamin C, dietary fiber, antioxidants), energy consumption, environmental sustainability, and quality control measures. Special emphasis is placed on the practical applicability of plum jam production in Uzbekistan’s agricultural context, its economic significance, and its potential in the global export market. The research is grounded in scientific literature, Uzbekistan’s normative-legal documents, and practical data from local enterprises. A comparative analysis of the advantages and limitations of each processing stage is provided, alongside recommendations for optimizing production processes, adopting modern technologies, and enhancing market competitiveness through organic certification and eco-friendly packaging. The article aims to contribute to the development of Uzbekistan’s food industry by proposing strategies for improving plum jam production efficiency and sustainability.